2019
DOI: 10.3847/1538-4357/aaf394
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Study of the Most Relaxed SPT-selected Galaxy Clusters: Properties of the Cool Core and Central Galaxy

Abstract: We present a multi-wavelength analysis of the four most relaxed clusters in the South Pole Telescope 2500 deg 2 survey, which lie at 0.55 < z < 0.75. This study, which utilizes new, deep data from the Chandra X-ray Observatory and Hubble Space Telescope, along with ground-based spectroscopy from Gemini and Magellan, improves significantly on previous studies in both depth and angular resolution, allowing us to directly compare to clusters at z ∼ 0. We find that the temperature, density, and entropy profiles of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…The Hogan et al (2017) clusters shown in the top panel were chosen mainly for their brightness, and are hence relatively representative of cool-core clusters. The bottom panel shows model fits to four objects from McDonald et al (2019a), which were selected to be the most dynamicallyrelaxed clusters out of the 100 clusters in the South Pole Telescope sample (SPT, Bleem et al 2015). The entropy profiles at 30 − 160 kpc of these clusters is steeper than in the sample shown in the top panel, and similar to the slope predicted by the cooling flow solution, especially in the Phoenix and SPT-CLJ2043-5035 clusters.…”
Section: Clustersmentioning
confidence: 77%
“…The Hogan et al (2017) clusters shown in the top panel were chosen mainly for their brightness, and are hence relatively representative of cool-core clusters. The bottom panel shows model fits to four objects from McDonald et al (2019a), which were selected to be the most dynamicallyrelaxed clusters out of the 100 clusters in the South Pole Telescope sample (SPT, Bleem et al 2015). The entropy profiles at 30 − 160 kpc of these clusters is steeper than in the sample shown in the top panel, and similar to the slope predicted by the cooling flow solution, especially in the Phoenix and SPT-CLJ2043-5035 clusters.…”
Section: Clustersmentioning
confidence: 77%
“…In order to compare the observed luminosity function with the expectations of different cosmological models, we need to adopt a mass calibration. At the moment, the 0.3 < z < 0.6 part of the CODEX scaling relations are not yet tightly constrained, while the available studies extending to a redshift of one argue in favor of the self-similar scaling for these relations outside of the cool core (McDonald et al 2019). Therefore, in this work we consider whether the observed lack of evolution of XLF can be explained by a combination of self-similar evolution of scaling relations and a change in some basic cosmological parameters, limiting the study to Ω M and σ 8 .…”
Section: Evolution Of Cluster X-ray Luminosity Functionmentioning
confidence: 96%
“…The systematic mass uncertainty amounts to 7.4%. Column 7: Chandra X-ray mass estimates computed by McDonald et al (2019) assuming the Y X -M scaling relation from Vikhlinin et al (2009). find any non-linear deviations of the multiplicative bias, but we note a shear dependence of the additive bias at |g| > 0.2.…”
Section: Discussionmentioning
confidence: 73%
“…To demonstrate the use of weak lensing measurements in the inner cluster and stronger shear regime we studied three clusters from the 2,500 deg 2 South Pole Telescope Sunyaev-Zel'dovich (SPT-SZ) Survey (Bleem et al 2015). According to their X-ray properties these three clusters are among the most relaxed clus-ters found in the SPT-SZ sample (McDonald et al 2019). These clusters are part of a larger sample of distant SPT-SZ clusters analysed using HST weak lensing data (S18a and S20).…”
Section: Hst Weak Lensing Measurements Of Three Highly Relaxed Cluste...mentioning
confidence: 99%
See 1 more Smart Citation